The BAR domain protein Arfaptin-1 controls secretory granule biogenesis at the trans-golgi network - Gehart, Helmuth; Beck, Rainer (Developmental cell, 2012)
Summary BAR domains can prevent membrane fission through their ability to shield necks of budding vesicles from fission-inducing factors. However, the physiological role of this inhibitory function and its regulation is unknown. Here we identify a checkpoint involving the BAR-domain-containing protein Arfaptin-1 that controls biogenesis of secretory granules at the trans-Golgi network (TGN). We demonstrate that protein kinase D (PKD) phosphorylates Arfaptin-1 at serine 132, which disrupts the ability of Arfaptin-1 to inhibit the activity of ADP ribosylation factor, an important component of the vesicle scission machinery. The physiological significance of this regulatory mechanism is evidenced by loss of glucose-stimulated insulin secretion due to granule scission defects in pancreatic β cells expressing nonphosphorylatable Arfaptin-1. Accordingly, depletion of Arfaptin-1 leads to the generation of small nonfunctional secretory granules. Hence, PKD-mediated Arfaptin-1 phosphorylation is necessary to ensure biogenesis of functional transport carriers at the TGN in regulated secretion.